Study on closing and cracking stress calculation method of fractured rock - Qiang, Yue; Liu, Gang; Xia, Changsi; Li, Shaohong; Li, Li; Zhao, Dongsheng; Zhou, Ling; Cheng, Longfei (Frontiers in Earth Science, 2023)
Determining the characteristic stress intensity according to rock stress-strain curve is of great significance for guiding rock engineering practice. At present, there are relatively mature methods for determining peak stress and damage stress, and the crack volume strain method, axial strain method, and strain response method for determining rock closure stress and crack initiation stress are more subjective. Based on these methods, the closure rock stress and crack initiation stress fine value method are proposed. The method is based on the discreteness of the rock stress and strain point. Through optimizing the stress characteristics by objective function (variance function), the subjectivity of artificial observation is avoided. At the same time, an empirical method determining closure rock stress and crack initiation stress is proposed. This method is based on the trend of the rock stress-strain curve. The test results indicate that the two proposed methods that compute closure rock stress and crack initiation stress can obtain reasonable results. This method can be used as a supplement to the characteristics of the rock stress determination method and can be used in actual engineering.